Unmet Mental Health and Social Service Needs of Formerly Incarcerated Women Living with HIV in the Deep South. (September 2018) - Pantalone, David W.; Scanlon, Michael L.; Brown, Shelley M.; Radhakrishnan, Bharathi; Sprague, Courtenay
Abstract : N/A: Due to the disproportionate burden of HIV among incarcerated women in the United States, jails and prisons have been identified as key sites for health service delivery. Recidivism remains high, potentially reflecting unmet mental health and social service needs of incarcerated women, especially during the postrelease adjustment period. However, little published research has investigated this possibility directly. We conducted semi‐structured, in‐depth interviews with previously incarcerated women living with HIV, and other key informants, and completed service‐availability mapping in two Alabama cities. Key findings were: (a) discharge planning and postrelease support services to manage risky environments were absent, (b) postrelease services were concentrated in a few community‐based organizations, (c) mental health and substance abuse treatment during re‐entry was essential to prevent relapse, and (d) social support was crucial for postrelease adjustment. We propose a novel conceptual model with key steps to establish continuous care for previously incarcerated women living with HIV.